Paeoniflorin directly binds to TNFR1 to regulate podocyte necroptosis in diabetic kidney disease - Wang, Xian; Liu, Xue-qi; Jiang, Ling; Huang, Yue-bo; Zeng, Han-xu; Zhu, Qi-jin; Qi, Xiang-ming; Wu, Yong-gui (Frontiers in Pharmacology, 2022)
Necroptosis was elevated in both tubulointerstitial and glomerular renal tissue in patients with diabetic kidney disease (DKD) and was most pronounced on glomerulus in the stage with macroalbuminuria. This study further explored whether paeoniflorin (PF) could affect podocyte necroptosis to protect kidney injure in vivo and in vitro. Our study firstly verified that there are obvious necroptosis-related changes in the glomeruli of DKD through bioinformatics analysis combined with clinicopathological data. STZ-induced mouse diabetes model and high-glucose induced podocyte injury model were used to evaluate the renoprotection, podocyte injury protection and necroptosis regulation of PF in DKD. Subsequently, the target protein-TNFR1 that PF acted on podocytes was found by computer target prediction, and then molecular docking and Surface plasmon resonance (SPR) experiments were performed to verify that PF had the ability to directly bind to TNFR1 protein. Finally, knockdown of TNFR1 on podocytes in vitro verified that PF mainly regulated the programmed necrosis of podocytes induced by high glucose through TNFR1. In conclusion, PF can directly bind and promote the degradation of TNFR1 in podocytes and then regulate the RIPK1/RIPK3 signaling pathway to affect necroptosis, thus preventing podocyte injury in DKD. Thus, TNFR1 may be used as a new potential target to treat DKD.